Relationship of Archus Pedis With Walking Balance In Children Aged 10-2 Years at SDN 017 Candirejo Air Molek - Bintang, Siti Sarah Bintang Sarah; Elvida Rahmi Zein; Annisa Nabila; Karnirius Harefa (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: WHO states the muskuloskeletal disorders disrupt the lives of hundreds of millions of individuals. The structure and biomechanics of the foot are greatly influenced by the arch of the foot. Abnormalities in the lower extremities often occur in children. Flat foot and cavus foot are disorders in the development of the arch of the foot. This condition can cause various problems, such as difficulty walking, impaired balance, easy fatigue when walking, frequent injuries, and excessive pain in the foot area. Purpose: This study aims to determine the relationship between the arch of the foot and walking balance in children aged 10-12 years at SDN 017 Candirejo Air Molek 2024. Research method This study applies a cross sectional approach design , namely , research to study the correlation between relationships with an observation approach and data collection at the same time. Results and discussion: The research results show that the variables related to the pedis arch (p-value = 0.000), walking balance (p-value = 0.000).Conslusion: Based on the research conducted that there is a relationship between the arch of the pedis and walking balance in children aged 10-12 years at SDN 017 Candirejo Air Molek 2024.